Cardiac Left Ventricle Mitochondrial Dysfunction After Neonatal Exposure to Hyperoxia: Relevance for Cardiomyopathy After Preterm Birth. Issue 3 (28th December 2021) - Ravizzoni Dartora, Daniela; Flahault, Adrien; Pontes, Carolina N.R.; He, Ying; Deprez, Alyson; Cloutier, Anik; Cagnone, Gaël; Gaub, Perrine; Altit, Gabriel; Bigras, Jean-Luc; Joyal, Jean-Sébastien; Mai Luu, Thuy; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Individuals born preterm present left ventricle changes and increased risk of cardiac diseases and heart failure. The pathophysiology of heart disease after preterm birth is incompletely understood. Mitochondria dysfunction is a hallmark of cardiomyopathy resulting in heart failure. We hypothesized that neonatal hyperoxia in rats, a recognized model simulating preterm birth conditions and resulting in oxygen-induced cardiomyopathy, induce left ventricle mitochondrial changes in juvenile rats. We also hypothesized that humanin, a mitochondrial-derived peptide, would be reduced in young adults born preterm. Methods: Sprague-Dawley pups were exposed to room air (controls) or 80% O2 at postnatal days 3 to 10 (oxygen-induced cardiomyopathy). We studied left ventricle mitochondrial changes in 4 weeks old males. In a cohort of young adults born preterm (n=55) and age-matched term (n=54), we compared circulating levels of humanin. Results: Compared with controls, oxygen-exposed rats showed smaller left ventricle mitochondria with disrupted integrity on electron microscopy, decreased oxidative phosphorylation, increased glycolysis markers, and reduced mitochondrial biogenesis and abundance. In oxygen-exposed rats, we observed lipid deposits, increased superoxide production (isolated cardiomyocytes), and reduced Nrf2 gene expression. In the cohort, left ventricle ejection fraction and peak global longitudinal strain were similar between groups however humanin levels were lower in preterm and associated with left ventricle ejection fraction and peak global longitudinal strain. Conclusions: In conclusion, neonatal hyperoxia impaired left ventricle mitochondrial structure and function in juvenile animals. Serum humanin level was reduced in preterm adults. This study suggests that preterm birth–related conditions entail left ventricle mitochondrial alterations that may underlie cardiac changes perpetuated into adulthood. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03261609.